PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SDN 61 HARAPAN BARU KECAMATAN MANDAU - wahyuni, Sri; Alpusari, Mahmud; Antosa, zairul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning sains study class IVC SD Negeri 61 Harapan Baru Kecamatan Mandau. From 20 students who achieve KKM just 8 students (40%) while student who did’nt complete 12 students (60%) with an average of 50,43. The purpose of this research to improve learning outcomes IPA class VB SDN 61 Harapan Baru with the application of learning models CTL. The results obtained by the average value of 50,43 basic score increased in the first cycle of 30,08% to 65,60. In the scond cycle the average value of students also increased by 48,52% to 74,90. On the basis of completeness score IPA student learning outcomes is only 50,43% (not finished). After application of the model Contextual Teaching and Learning (CTL) by techers  in the first cycle classical completeness increased to 50% (not finished) ,the second cycle classical completeness obtained are increased to increase to 85% activities of teachers at the first meeting of 56% with enougg categories. The second meeting increased to 75% in both categories . In the second cycle increased to 87% with the category very well. At  a meeting of the second meeting of the second cycle, the activities of teachers increased to 93% with the category very well. Activities of studentsin the first cycle of thr first meeting activity students acquire a percentage of 62% in enough categories. The second meeting of the first cycle to 75%  in both categories. At the first  meeting of  the scond cycle of students activity increased to 81% with the categoryvery well,and at the second meeting of the second cycle increased again to 93% with the category very well. Key words : Contextual Teaching end Learning, learning outcomes IPA